2010
DOI: 10.2135/cropsci2009.08.0455
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Forage Quality from Remotely Sensed Data: Comparison of Cultivar‐Specific and Cultivar‐Independent Equations Using Three Methods of Calibration

Abstract: RESEARCHT he study findings suggested that cultivar-specifi c (CS) equations were not necessary for prediction of N concentration. Both cultivar-independent (CI) and CS neutral detergent fi ber (NDF) and acid detergent fi ber (ADF) equations revealed poor to moderate performance. Comparison of partial least square (PLS), multiple linear regression with maximum r 2 improvement (MAXR), and artifi cial neural network (ANN) calibration and validation results revealed that ANN rarely outperformed PLS and MAXR. Auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…Our results confirmed that sugarcane leaf relative chlorophyll and N contents could be well estimated across a wide range of genotypes and throughout the growing season (Table 4). This is consistent with early reports in other crops (Carter and Estep, 2002; Zhao et al, 2005a, 2005b; Starks and Brown, 2010).…”
Section: Results and Disscussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results confirmed that sugarcane leaf relative chlorophyll and N contents could be well estimated across a wide range of genotypes and throughout the growing season (Table 4). This is consistent with early reports in other crops (Carter and Estep, 2002; Zhao et al, 2005a, 2005b; Starks and Brown, 2010).…”
Section: Results and Disscussionsupporting
confidence: 93%
“…Leaf chemical composition (SPAD, N and C contents, and C to N ratio), yield components ( juice sucrose, TCH, CRS, and TSH), and leaf refl ectance data were randomly assigned into two groups (i.e., two independent datasets with equal numbers of genotypes). The trailing dataset was used to develop leaf refl ectance models for prediction of leaf chemical and yield traits using the methods of maximum r 2 improvement (MAXR) regression (Zhao et al, 2007) and partial least-square (PLS) regression (Starks and Brown, 2010) under PROC REG and PROC PLS, respectively, in SAS statistical software (SAS Institute, 2007). The second dataset was used for model validations.…”
Section: Calibration Equation Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…An R 2 = 0.82 was reported by Starks et al (2008) for N concentration to spectral reflectance in the 705‐ to 1685‐nm range in warm‐season grass pastures. Starks and Brown (2010) noted no cultivar‐specific model offered an advantage in improving estimation accuracy for N concentrations of three bermudagrass cultivars using hyperspectral reflectance measurements from 350 to 1125 nm. Guo et al (2010) observed R 2 values of 0.63 for forage CP estimation when hyperspectral data in the 350‐ to 2500‐nm range were collected in a semiarid, mixed‐prairie ecosystem.…”
mentioning
confidence: 99%
“…The variation inherent in the sample population studied could be increased when the sample set consists of a number of heterogeneous samples. However, the development of separate vis-NIR calibrations for different crop species requires more efforts and resources for calibrations and periodic validations than the use of a global calibration model (Shenk et al, 1979;Starks and Brown, 2010). Use of the local (e.g., species-specific) calibrations may therefore be preferable in applications requiring maximum precision.…”
Section: Homogeneity Of Calibration Subsetsmentioning
confidence: 99%